Teachers' knowledge and issues in the implementation of school-based assessment: A case of schools in Terengganu / Raja Nurul Huda Raja Zahri - Raja Zahri, Raja Nurul Huda (2013)
In tandem with educational best practices the world over, School-based assessments (SBAs) were introduced in Malaysia in 2012 for secondary one students. This study investigated quantitatively and qualitatively matters such as the teachers' knowledge of SBAs and the issues faced when implementing SBAs, whereas the factors contributing to the problems of SBA implementation was investigated only qualitatively. A sample of 60 English teachers in the district of Dungun, Terengganu, who were involved in SBAs from the beginning were chosen as respondents. Out of this, 20 teachers were interviewed to obtain qualitative findings. It was found that teachers had satisfactory knowledge of planning an SBA-tailored lesson. They also showed satisfactory knowledge of developing SBAs but appeared to have difficulty in the psychometrics of test analysis. As for issues faced by teachers, they were not indifferent to SBA implementation but team work and collaboration among SBA teachers needs to be improved. Teachers faced problems in SBA implementation but overall had a positive attitude towards SBA. Teachers voiced concerns over the lack of adequate staff numbers, lack of uniformity and a possible element of biasness in grading. Teachers also faced time constraints, lack of effective materials and methodologies and poor ICT facilities in schools. They also feared cheating by students in SBAs. The findings have important implication in introducing best practices into SBA such as consistency and uniformity of grading and impartiality of teachers. Future researchers should investigate the success of SBA implementation after a few years.